Complementarity and conflict: An Andean vision of man and woman - Harris, Olivia (1985)
The analysis of binary conceptual systems includes "man and woman" as paradigms of opposite categories. In many cultures, the use of the categories "woman and man", to facilitate thinking, seems to be part of an ordering system in which women are placed on the less valued and inferred side of the opposition. Thus, some authors have suggested that women are to men, what nature is to culture. Others have drawn attention to the way in which the left or right hand is used to express gender differences, in the words of Evans Pritchard, "a slight organic asymmetry becomes a symbol of an absolute moral polarity" (1973).